2015
DOI: 10.18632/oncotarget.4576
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive molecular pathology analysis of small bowel adenocarcinoma reveals novel targets with potential for clinical utility

Abstract: Small bowel accounts for only 0.5% of cancer cases in the US but incidence rates have been rising at 2.4% per year over the past decade. One-third of these are adenocarcinomas but little is known about their molecular pathology and no molecular markers are available for clinical use.Using a retrospective 28 patient matched normal-tumor cohort, next-generation sequencing, gene expression arrays and CpG methylation arrays were used for molecular profiling.Next-generation sequencing identified novel mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 29 publications
3
49
3
Order By: Relevance
“…For instance, abnormal p53 is frequently observed (41-42%) and is associated with poor prognosis. 29,[33][34][35] Alteration of p53 is considered a late step in the adenoma-to-carcinoma sequence, as no additional mutations are likely needed to complete carcinogenesis, given its profound tumor suppressor activity. Another tumor suppressor, p16, or CDKN2A, which inhibits the cell cycle, is also increased in SBA.…”
Section: Genetics and Molecular Biologymentioning
confidence: 99%
“…For instance, abnormal p53 is frequently observed (41-42%) and is associated with poor prognosis. 29,[33][34][35] Alteration of p53 is considered a late step in the adenoma-to-carcinoma sequence, as no additional mutations are likely needed to complete carcinogenesis, given its profound tumor suppressor activity. Another tumor suppressor, p16, or CDKN2A, which inhibits the cell cycle, is also increased in SBA.…”
Section: Genetics and Molecular Biologymentioning
confidence: 99%
“…For example, IDH1 and IDH2 mutations are present in approximately 16%–36% of intrahepatic BTCs, but are more rare in other solid malignancies . We identified only five cases from two series in the literature of IDH1 mutations in small intestinal adenocarcinoma, all of which occurred in the ileum . In this case, identification of an IDH1 mutation in both ctDNA and tissue made the diagnosis of duodenal adenocarcinoma unlikely and suggested a pancreaticobiliary cancer was the true diagnosis.…”
Section: Molecular Tumor Boardmentioning
confidence: 92%
“…The low rate of APC alterations in SBA compared with CRC has been noted in prior smaller studies and represents one of the most fundamental genomic differences between large bowel adenocarcinoma and SBA. [54][55][56][57] In another comparative analysis of copy number changes between SBA, CRC, and gastric cancer, unsupervised clustering showed that SBA clustered more commonly with CRC than gastric cancer. 58 Another critical molecular insight relates to the comparison of molecular alterations across the different small bowel subsites: duodenum, jejunum, and ileum.…”
Section: Molecular Alterationsmentioning
confidence: 99%